Analisis kemurnian dan konsentrasi DNA hasil isolasi pada pembuatan DNA baku spesies tikus: Analisis kemurnian dan konsentrasi DNA hasil isolasi pada pembuatan DNA baku spesies tikus - Alfi Sophian; Andi Syukur (Badan Pengawas Obat dan Makanan, 2021)
Analysis of the purity and concentration of isolated DNA in the manufacture of standard rat DNA was carried out to see whether the isolation carried out could produce good quality DNA. The purpose of this study is to provide information on the manufacture of raw DNA in species DNA testing where the raw material that has been purchased so far made from synthetic materials can be more economical if using DNA material derived from the meat raw material of the target species. The DNA extraction method used is the column spin method or column centrifuge using the Intron Patho Gene-Spin (Viral DNA/RNA) extraction kit. Analysis method of concentration and purity of isolated DNA was analyzed based on the average value of concentration and purity which was read using a nanophotometer. Based on the results of the research conducted, the results of the isolated DNA concentration values ​​were in the concentration range of 41,250 ng/ mL to 42,300 ng/mL, with the average concentration of isolated DNA was 41,777 ng/mL. For the value of the purity of the isolated DNA whose absorbance was read using a nanophotometer at a wavelength of A260/A280, the results were between 2,301 to 2,384 with the average value of purity being at 2,326. This study concludes that all the extracted samples that showed the results of the DNA analysis produced were included in the good DNA category.